Bronchoscopic lung volume reduction complicated by ipsilateral pleural effusion - Marc Assaad; Wasif Shamsi; Anthony Loschner; Maria del Mar Cirino-Marcano (Respiratory Medicine Case Reports)
Chronic obstructive lung disease is the third leading cause of death worldwide. It affects the airways and lung parenchyma leading to emphysema. Bronchoscopic lung volume reduction is another strategy that aims to reduce air trapping and hyperinflation, leading to improvement in symptoms and pulmonary function. Several techniques have been employed, one of them is the blocking method using Zephyr or Spiration valves. The use of both valves is approved by the Food and Drug Administration view their established efficacy in improving lung functions, quality of life and survival. Although they have a relatively safe profile, several adverse events have been reported, pneumothorax being the most common and pleural effusion being the least reported. We show herein, a case of 74-year-old female presenting with pleural effusion secondary to bronchoscopic lung volume reduction. Although uncommon, highlighting this potential outcome is crucial.